A synergy effect of internationalization and firm size on performance: US hotel industry. Issue 1 (4th February 2014) - Lee, Seoki; Upneja, Arun; Özdemir, Özgür; Sun, Kyung-A
Abstract : Purpose: – The purpose of the current study is to investigate the existence of a negative synergy effect of internationalization and firm size on firm performance for publicly traded US hotels. Design/methodology/approach: – The study performs the two-way fixed-effects model to investigate the proposed negative synergy effect. Findings: – The findings do not support the proposed negative synergy effect, but support the positive synergy effect of internationalization and firm size on performance. Originality/value: – This study examines the hypothesis developed based on the agency cost theory using the hotel industry's unique monitoring cost argument. However, findings support the opposite, implicitly suggesting that the hotel's monitoring cost in the international franchising context may not be severe as some expect.